A de novo assembled genome of the Tibetan Partridge (Perdix hodgsoniae) and its high‐altitude adaptation. Issue 2 (26th September 2022) - LI, Xuejuan; WANG, Xiaoyang; YANG, Chao; LIN, Liliang; YUAN, Hao; LEI, Fumin; HUANG, Yuan
Abstract: The Tibetan Partridge ( Perdix hodgsoniae ) is an endemic species distributed in high‐altitude areas of 3600–5600 m on the Qinghai–Tibet Plateau. To explore how the species is adapted to the high elevation environment, we assembled a draft genome based on both the Illumina and PacBio sequencing platforms with its population genetics and genomics analysis. In total, 134.74 Gb short reads and 30.81 Gb long reads raw data were generated. The 1.05‐Gb assembled genome had a contig N50 of 4.56 Mb, with 91.94% complete BUSCOs. The 17 457 genes were annotated, and 11.35% of the genome was composed of repeat sequences. The phylogenetic tree showed that P. hodgsoniae was located at the basal position of the clade, including Golden Pheasant ( Chrysolophus pictus ), Common Pheasant ( Phasianus colchicus ), and Mikado Pheasant ( Syrmaticus mikado ). We found that 1014, 2595, and 2732 of the 6641 one‐to‐one orthologous genes were under positive selection in P. hodgsoniae, detected using PAML, BUSTED, and aBSREL programs, respectively, of which 965 genes were common under positive selection with 3 different programs. Several positively selected genes and immunity pathways relevant to high‐altitude adaptation were detected. Gene family evolution showed that 99 gene families experienced significant expansion events, while 6 gene families were under contraction. The total number of olfactory receptor genes was relatively low in P. hodgsoniae . Genomic data provide an important resource for a further study on the evolutionary history of P. hodgsoniae, which provides a new insight into its high‐altitude adaptation mechanisms. Abstract : This paper has presented a high‐quality reference genome of the Qinghai–Tibet Plateau endemic species, Tibetan Partridge ( Perdix hodgsoniae ). The comparative genome analysis has revealed that P. hodgsoniae clustered with the clade of C. pictus / P. colchicus / S. mikado, and split at 21.3 Mya. The study of high‐altitude adaptation has found some PSGs annotated in the cellular response to DNA damage stimulus and DNA repair in reaction to UV radiation, and several immunity pathways such as the Toll‐like receptor signaling pathway, cytokine‐cytokine receptor interaction, and MAPK signaling pathway.